The natural flavonoid silybin improves the response to Photodynamic Therapy of bladder cancer cells - Gándara, Lautaro (2014)
Photodynamic Therapy (PDT) is an anticancer treatment based on photosensitisation of malignant cells. The precursor of the photosensitiser Protoporphyrin IX, 5-aminolevulinic acid (ALA), has been used for PDT of bladder cancer. Silybin is a flavonoid extracted from Silybum marianum, and it has been reported to increase the efficacy of several anticancer treatments. In the present work, we evaluated the cytotoxicity of the combination of ALA?PDT and silybin in the T24 and MB49 bladder cancer cell lines. MB49 cells were more sensitive to PDT damage, which was correlated with a higher Protoporphyrin IX production from ALA. Employing lethal light doses 50% (LD50) and 75% (LD75) and additional silybin treatment, there was a further increase of toxicity driven by PDT in both cell lines. Using the Chou?Talalay model for drug combination derived from the mass-action law principle, it was possible to identify the effect of the combination as synergic when using LD75, whilst the use of LD50 led to an additive effect on MB49 cells. On the other hand, the drug combination turned out to be nearly additive on T24 cells. Apoptotic cell death is involved both in silybin and PDT cytotoxicity in the MB49 line but there is no apparent correlation with the additive or synergic effect observed on cell viability. On the other hand, we found an enhancement of the PDT-driven impairment of cell migration on both cell lines as a consequence of silybin treatment. Overall, our results suggest that the combination of silybin and ALA-PDT would increase PDT outcome, leading to additive or synergistic effects and possibly impairing the occurrence of metastases. 2014 Elsevier B.V. All rights reserved